Impact of deep brain stimulation on pharyngo‐esophageal motility: a randomized cross‐over study. Issue 9 (5th June 2015) - Derrey, S.; Chastan, N.; Maltete, D.; Verin, E.; Dechelotte, P.; Lefaucheur, R.; Proust, F.; Freger, P.; Leroi, A. M.; Weber, J.; Gourcerol, G.
Abstract Background Bilateral subthalamic nucleus (STN) stimulation is used to alleviate Parkinson's disease (PD) motor symptoms. Recently, it has been shown that this therapeutic also increased gut cholinergic contractions. We therefore investigated the effect of STN stimulation on esophageal motility in an interventional randomized study. Methods Sixteen humans PD patients (4 women, 12 men; age: 62.4 ± 9.3‐years old) who underwent STN stimulation for at least 6 months were randomly evaluated with either stimulator turned OFF then ON, or inversely. Esophageal high resolution manometry was performed at the end of each ON and OFF period, with a 5 min resting period followed by ten swallows of 5 mL. Key Results During the ON, an increase in the distal contractility index was found (OFF: 1750 ± 629 vs ON: 2171 ± 755 mmHg/cm/s; p = 0.03), with no difference in the distal front velocity. A decrease in the integrative relaxation pressure of the lower esophageal sphincter (LES) was noted (OFF: 11.1 ± 1.8 mmHg vs ON: 7.2 ± 1.8 mmHg; p < 0.05) in ON. The LES resting pressure remained unchanged during the two periods. This resulted in a decrease in the intrabolus pressure (p = 0.03). No difference was observed for the upper esophageal sphincter, nor the pharyngeal contraction amplitude and velocity. Conclusions & Inferences In conclusion, STN stimulation in PD patients increased esophageal body contractions and enhanced the LES opening. This suggests that the nigrostriatal‐striatonigral loop is involved in the control of esophageal motility.